Effects of Bed Height and Particle Size on Drying of a Turkish Lignite - Pusat, Saban; Akkoyunlu, Mustafa Tahir; Erdem, Hasan Huseyin; Teke, Ismail (TAYLOR & FRANCIS INC, 2015)
Drying of coarse lignite particles, because of high inherent moisture content, is very important for the lignite user. An effective drying process is necessary to utilize coarse lignite particles effectively. Fixed-bed drying experiments were carried out for a Turkish lignite (Konya-Ilgin). Effects of bed height and particle size were investigated. Drying experiments were carried out at 80, 130, and 150 mm bed heights and 20, 35, and 50 mm particle sizes. It was found that increasing the bed height increased the drying time and decreased the drying rate, and particles of larger sizes have lower drying rates and higher drying times. Additionally, it was also found that Konya-Ilgin lignite does not show a constant drying rate and has a long falling drying rate. As a result of this study, drying characteristics of Konya-Ilgin lignite were presented for different drying conditions.
Keywords: Bed height; Drying kinetics; Fixed bed; Lignite; Low-rank coal; Particle size; TEMPERATURE; MICROWAVE; CHINESE; FLUIDIZATION; Energy & Fuels; Mining & Mineral Processing